Nowa narracja wojenna: kobiety ukraińskie w obliczu konfliktu zbrojnego - Nowacki, Albert (Studia Ukrainica Posnaniensia, 2025)
This article explores the multidimensional roles of Ukrainian women in the realities of the Russian-Ukrainian war, highlighting their active engagement both on the front lines and in civilian support structures. It examines the transformation in the image of women, portraying them not only as victims but also as soldiers, medics, volunteers, journalists, and chroniclers. Particular attention is given to the emotional responses of women to war-fear, anger, and determination – and their role in fostering resistance, social cohesion, and national identity. Ukrainian women are thus redefining wartime narratives by combining courage and agency with care and responsibility for the future of their communities.